Letter from Winthrop Ames to Mrs. Jabez Fox (21 April 1910) - Ames, Winthrop, 1870-1937 (author):::Creator::::::::::::; Fox, Susan Thayer, 1853-1930 (recipient):::Contributor:::::::::::: (New York, NY; United States, 2023)
Photocopy of a typewritten letter from Winthrop Ames, director of the New Theatre in New York, to Susan Thayer Fox (Mrs. Jabez Fox), niece of Alexander Wheelock Thayer, asking if the "relics" loaned from Thayer's Beethoven collection for an exhibition during a theater production of the play "Beethoven" could be kept until the end April 30, 1910, the end of the play's run.